Optimizing Investment Portfolios with Bacterial Foraging and Robust Risk Management - Hubert Zarzycki (Algorithms, 2025)
This study introduces a novel portfolio optimization approach that combines Bacterial Foraging Optimization (BFO) with risk management techniques and Sharpe ratio analysis. BFO, a nature-inspired algorithm, is employed to construct diversified portfolios, while risk management strategies, including stop-loss limits and transaction cost considerations, enhance risk control. The Sharpe ratio is used to evaluate the efficiency of the investment strategy by accounting for risk-adjusted returns. The experiments demonstrate that this approach effectively balances risk and return, making it a valuable tool for portfolio management in dynamic financial markets.